2014
DOI: 10.1111/ajgw.12110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofLactobacillus plantarumandOenococcus oeniduring spontaneous malolactic fermentation in Patagonian red wines revealed by polymerase chain reaction-denaturing gradient gel electrophoresis with two targeted genes

Abstract: Background and Aims Information regarding the composition and dynamics of microbial communities throughout winemaking is always valuable to control the process and contributes to improving the quality of wine. The aims of this work were to analyse the diversity of lactic acid bacteria (LAB) species present during the spontaneous malolactic fermentation (MLF) of Patagonian red wines, and to isolate and identify native LAB species. Methods and Results Samples of Merlot and Pinot Noir wines were collected during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…During spontaneous MLF, O. oeni is the major bacterial species found, however, several species can be occasionally detected, mainly Lactobacillus, Pediococcus, and Leuconostoc [1,19]. In some of the warmer wine growing regions, L. plantarum is more frequently isolated from spontaneous malolactic fermentations [13,[21][22][23]. Lerm et al reported three O. oeni and three L. plantarum strains from South Africa wine isolates for use as MLF starter cultures.…”
Section: Biodiversity Of Lactic Acid Bacteria In Winementioning
confidence: 99%
See 1 more Smart Citation
“…During spontaneous MLF, O. oeni is the major bacterial species found, however, several species can be occasionally detected, mainly Lactobacillus, Pediococcus, and Leuconostoc [1,19]. In some of the warmer wine growing regions, L. plantarum is more frequently isolated from spontaneous malolactic fermentations [13,[21][22][23]. Lerm et al reported three O. oeni and three L. plantarum strains from South Africa wine isolates for use as MLF starter cultures.…”
Section: Biodiversity Of Lactic Acid Bacteria In Winementioning
confidence: 99%
“…Lerm et al reported three O. oeni and three L. plantarum strains from South Africa wine isolates for use as MLF starter cultures. Bergeral et al [21] had studied the properties of Lactobacillus plantarum strains isolated from grape must fermentation Apulian wines in order to select suitable starter for MLF, and Valdés La Hens et al [22] reported the Prevalence of L. plantarum and O. oeni during spontaneous fermentation in Patagonian red wines. More recently, Lópes-Seijas et al [23] evaluated malolactic bacteria associated with wine from the Albariño variety.…”
Section: Biodiversity Of Lactic Acid Bacteria In Winementioning
confidence: 99%
“…plantarum is commonly found in wine (Edwards et al 1993, Beneduce et al 2004, G-Alegria et al 2004, Ruiz et al 2010a, and has been associated with spontaneous MLF in, for example, Patagonian red wines (Valdés La Hens et al 2015). plantarum is commonly found in wine (Edwards et al 1993, Beneduce et al 2004, G-Alegria et al 2004, Ruiz et al 2010a, and has been associated with spontaneous MLF in, for example, Patagonian red wines (Valdés La Hens et al 2015).…”
Section: Applications Of L Plantarum In Mlfmentioning
confidence: 99%
“…L. plantarum is commonly found in wine (Edwards et al 1993, Beneduce et al 2004, G-Alegria et al 2004, Ruiz et al 2010a, and has been associated with spontaneous MLF in, for example, Patagonian red wines (Valdés La Hens et al 2015). This bacterium is homofermentative for hexoses such as glucose (Fugelsang and Edwards 2007); it will produce only lactic acid and not acetic acid when it metabolises glucose, thus eliminating any potential risk of contributing to volatile acidity.…”
Section: Applications Of L Plantarum In Mlfmentioning
confidence: 99%
“…Several studies intending to elucidate the presence, distribution, and adaptation of wine associated LAB have already been performed in wineries from regions with an extensive winemaking tradition, such as Mentrida (Pérez-Martín et al, 2014), La Rioja (González-Arenzana et al, 2015), Patagonia (La Hens et al, 2015), and Apulia (Garofalo et al, 2015). However, this kind of studies are missing in areas where the development of this industry is recent, like Queretaro State in Mexico.…”
Section: Introductionmentioning
confidence: 99%